Minimnya Penggunaan Media Sosial Sebagai Sarana Komunikasi Injil oleh Pemuda Kristen di Abad 21 - Tansi, Filmon Gusti; Beriang, Senan (Sekolah Tinggi Teologi Immanuel Sintang Kal-Bar, 2023)
In modern life, especially in the 21st century, the influence of technological developments is very rapid, including the presence of social media (social media) and it has become a basic need for humanity in the technological era and not to forget the church as a place for people to worship. Every congregation within the church environment has known and used social media for various things including facilitating congregations to read the Bible, electronic hymnbooks and so on. However, it seems that there are still some congregations who are less responsive in using social media wisely. Christian youth in the 21st century, who are the majority of active social media users, seem less aware of this opportunity, so they experience difficulties in preaching the Gospel to others. For this reason, the aim of this research is to provide good knowledge so that Christian youth in the 21st century can utilize social media as a means of preaching the Gospel based on the Great Commission. The method used in this scientific work is a qualitative research method, by means of observation, interviews and documentation. The author chose this type of research because the author wanted to find out why there was a lack of response from Christian youth in the 21st century in utilizing social media as a means of preaching the gospel. The results of this scientific work are to raise awareness of Christian youth regarding the importance of using social media in preaching the Gospel.